Central cannulation strategy for extent I thoracoabdominal aneurysm repair of chronic type B aortic dissection. Issue 8 (10th July 2017) - Hobbs, Reilly D.; Wallen, Tyler J.; Komlo, Caroline M.; Moeller, Patrick J.; Pochettino, Alberto; Bavaria, Joseph E.; Vallabhajosyula, Prashanth
Abstract: Introduction: We evaluated the safety profile of a central cardiopulmonary bypass (CPB) cannulation strategy for repair of extent I thoracoabdominal aortic aneurysms (TAAA) with chronic type B dissection in comparison to traditional peripheral CPB cannulation strategies. Methods: Patients undergoing extent I TAAA repair for chronic type B dissection from 2002 to 2011 were retrospectively reviewed. Patients were grouped by their CPB cannulation strategy. Patients in Group I underwent central aortic cannulation (n = 28) through a left thoracotomy incision. The true lumen of the descending thoracic aorta was cannulated using an echocardiogram‐guided Seldinger wire technique. The right atrium was directly accessed for venous drainage. In Group II (n = 31), arterial and venous cannulation of the femoral vessels was achieved using a left‐sided groin incision. All patients underwent deep hypothermic circulatory arrest for proximal aortic reconstruction. Results: Preoperative aortic dimensions (6.5 ± 0.79 cm in Group I vs 7.0 ± 1.15 cm in Group II p = 0.8) were similar between groups. CPB time (240 ± 37 min in Group I vs 174 ± 68 min in Group II p < 0.01) was significantly higher in the central cannulation group whereas circulatory arrest times (43 ± 5 min Group I vs 37 ± 7 min in Group II p = 0.1) were similar between the two groups. In‐hospital 30‐day mortality (N = 0, 0% in Group I; N = 2, 6.5% in Group II), stroke (N = 1, 3.5% in Group I; N = 0, 0% in Group II), paraplegia (N = 1, 3.5% in Group I; N = 1, 3.2% in Group II), reoperation for bleeding (N = 1, 3.5% in Group I; N = 1, 3.2% Group II), tracheostomy rate (N = 2, 7% in Group I; N = 3, 9.7% Group II), and mean length of stay (19 days in Group I vs 17 days in Group II) were similar (p > 0.05). Median follow‐up was 3.6 ± 2.0 in Group I and 5.6 ± 2.6 years in Group II. Actuarial survival at 5 years was 84.6 % for Group I and 77.6% for Group II (p = 0.52). Conclusions: Central true lumen cannulation through a left thoracotomy incision for repair of extent I TAAA with chronic type B dissection is an acceptable approach with equivalent early and midterm outcomes compared to more standard femoral cannulation techniques. It may provide a safe alternative cannulation site for patients with diseased femoral vessels.